2011
DOI: 10.1080/09500340.2011.618890
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation in young adults wearing aspheric multifocal soft contact lenses

Abstract: The aim of the present project was to investigate accommodative behavior in young adults and adolescents fitted with an aspheric multifocal (center distance) contact lens with focus on evaluating whether these lenses can be an alternative treatment for subjects in which a reduced level of blur and thereby accommodation in near vision is aimed at. Twenty normal subjects aged between 21 and 35 years participated in the study. Aberrometry was perfomed using a Zywave TM aberrometer, first on the uncorrected eyes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…However, the present study's cohort, selected to have manifest accommodative lag and symptoms of asthenopia, failed to exhibit any significant change in lag for any contact lens condition, despite a marked improvement in CISS score with multifocal contact lens wear. This finding is, however, consistent with several other studies which have used centre-near [38,39,[55][56][57] or centredistance multifocal lenses [35] and have detected no significant change in accommodative lag compared to single vision distance contact lenses. Conversely, some studies have reported an increase in lag [34,35,58], while one study investigating bifocal contact lenses found that lag decreased [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the present study's cohort, selected to have manifest accommodative lag and symptoms of asthenopia, failed to exhibit any significant change in lag for any contact lens condition, despite a marked improvement in CISS score with multifocal contact lens wear. This finding is, however, consistent with several other studies which have used centre-near [38,39,[55][56][57] or centredistance multifocal lenses [35] and have detected no significant change in accommodative lag compared to single vision distance contact lenses. Conversely, some studies have reported an increase in lag [34,35,58], while one study investigating bifocal contact lenses found that lag decreased [20].…”
Section: Discussionsupporting
confidence: 92%
“…Although multifocal soft contact lenses were originally designed to incorporate a near addition prescription in the contact lens to provide clearer vision for presbyopes, studies have suggested that multifocal soft contact lenses could also be used as a possible correcting option to reduce accommodation and binocular dysfunction of pre-presbyopes [34][35][36][37][38][39]. However, the ability of multifocal soft contact lenses as a successful treatment option for ocular asthenopia varies, and is not entirely understood [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which MCLs interact with accommodation has been explored in some studies. Petterson et al [ 19 ] found similar accommodation in pre-presbyopic adults when subjects were wearing bifocal center-distance corrections as compared to their lag with single vision lenses, suggesting that young subjects do not relax their accommodation with multifocal aspheric contact lenses. However, this is in contrast with the results of a study on accommodation dynamics with induced spherical aberration (using adaptive optics), which showed that accommodative lag is modulated differently by the presence of positive spherical aberration (equivalent to center- distance add) or negative spherical aberration (equivalent to center-near add) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process ensures that a patient is able to see clearly both at distance and near (Benjamin 2006). However, 8% of children and young adults have accommodation dysfunctions, which is regarded as one aspect of myopization process in children (Pettersson et al 2011). Accommodation errors which occur in the event of the accommodative lag place the focus behind the fixation point, leading thus to accommodative insufficiency.…”
Section: Introductionmentioning
confidence: 99%